A single polypyrimidine tract binding protein (PTB) binding site mediates splicing inhibition at mouse IgM exons M1 and M2 - SHEN, HAIHONG (Copyright 2004 by RNA Society, 2004)
Splicing of mouse immunoglobulin (IgM) exons M1 and M2 is directed by two juxtaposed regulatory elements, an enhancer and an inhibitor, located within the M2 exon. A primary function of the enhancer is to counteract the inhibitor, allowing splicing to occur. Here we show that the inhibitor contains two binding sites for polypyrimidine tract binding protein (PTB). Mutational analysis indicates that only one of these sites is necessary and sufficient to direct splicing inhibition both in vitro and in vivo. We demonstrate that the difference in activity of the two sites is explained by proximity to the intron. We further show that the presence of the enhancer results in the disruption of the PTB-inhibitor interaction, enabling splicing to occur. In the absence of the enhancer, splicing can be artificially activated by immuno-inhibition of PTB. Collectively, our results indicate that a single PTB binding site can function as an inhibitor that regulates alternative splicing both in vitro and in vivo.